Current state and prospects for the development of tourism, including agritourism, in the Republic of Moldova - Roman, Michał (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The article aims to present the essence of the development of tourism in the Republic of Moldova. It draws attention to the attractiveness of tourism in the context of the development of the region and the social-cultural values of the country’s rural areas. The article makes use of the database of the World Tourism Organisation, the National Bureau of Statistics of the Republic of Moldova and information collected during study visits to the staff of the Association of Tourism Development in Moldova (in Kishinev, the capital city of Moldova, in June and July 2016). Moldova is a small country with a lot of tourist attractions. There are over 15,000 anthropogenic attractions for tourists and over 300 nature areas. In 2014, 96,000 tourists visited Moldova (7.5% more than in the preceding year), generating $226 million in revenues. There were seven providers of tourist services in 2005, and there were already 26 in 2015. The author was a co-founder of four agritourism clusters in Moldova developed within an international project
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 473, s. 455-467
Keywords: tourism; tourist movement; rural tourism; agritourism; Moldova; turystyka; ruch turystyczny; turystyka wiejska; agroturystyka; Mołdawia